Producing investment returns at the margin of finance: a frontier talent proposition - Urban, M (Elsevier, 2018)
Institutional investment management requires expertise. In the “war-for-talent”, co-located private sector financial institutions drive wages up, thereby side-lining resource-constrained public pension funds and forcing them to outsource their investment functions. This article develops a frontier talent proposition based on a case-study of an atypical and exemplary U.S. public pension plan that produces competitive investment returns at-a-distance (geographically and economically) from financial agglomerations by internally managing 75 bn USD of retirement assets on a tight budget. Combining labour market statistics and close-dialogue with 37 investment professionals, the case-study documents original comparative advantages of the periphery relative to financial agglomerations in talent recruitment. It contributes new insights on geographical differences in real wages and the quality of life of finance workers. Looking ahead, the article suggests the relevance of frontier talent to a larger set of financial institutions facing increasing difficulties to staff their organisations in top-tier financial centres.